Evaluation of the incidence of radial artery occlusion using different introducer sheaths and hemostasis techniques. Issue 3 (16th July 2022) - Patel, Purveshkumar; Sethi, Nishant; Patel, Gaurav A.; Kalisetti, Deepika; Patel, Tejas M.
Abstract: Background: Radial artery occlusion (RAO) remains one of the most important complications of transradial access (TRA). Despite the identification of multiple predictors, the interaction between these predictors on the occurrence of RAO has not been evaluated. Methods: Consecutive patients undergoing TRA coronary angiography (CA) or percutaneous coronary intervention (PCI), were retrospectively analyzed to compare the effect of standard patent hemostasis using a one‐bladder band versus two‐bladder band with simultaneous ipsilateral ulnar artery compression and two introducer sizes on the primary endpoint of RAO. Access was obtained using 6‐Fr slender introducer sheath or 7‐Fr slender introducer sheath and hemostasis with either a one‐bladder band or a two‐bladder band. The radial artery was evaluated using ultrasound. Results: Total of 2019 patients undergoing CA or PCI were included in the analysis. In the one‐bladder band group, the incidence of RAO with a 6‐Fr slender introducer sheath was 4.2%. In those receiving hemostasis with a two‐bladder band, RAO occurred in 1% of patients receiving a 6‐Fr slender introducer sheath versus 0.9% in those receiving a 7‐Fr slender introducer sheath ( p  = 0.68). Larger radial artery diameter, larger body weight, and a two‐bladder hemostasis band with ipsilateral ulnar compression were independently associated with a lower incidence of RAO. Conclusion: A two‐bladder band with simultaneous ipsilateral ulnar artery compression when used for radial artery hemostasis, is associated with a lower incidence of RAO, and can mitigate the penalty for a larger catheter with reassuring implications for use of a 7‐Fr capable system for complex transradial PCI.